Iniquidades em saúde entre servidores públicos municipais: influência das condições de trabalho e impacto sobre a capacidade para o trabalho - Marcus Alessandro de Alcantara (2013)
Introduction: Evidences shows that socioeconomic inequalities are associated with poorer self-rated health, morbidity and mortality. The unequal distribution of indicators such as income and education and the differential access of the social groups to services and health care are potential explanations for such disparities. Recently, studies have examined the contribution of the working conditions as explanation for inequities in health and the results suggest that precarious workingconditions can result in serious social and economic consequences and compromise the health of workers. The health, in conjunction with other resources of the individual such as functional capability, knowledge and skill, is crucial for the workers maintain good work ability and prolong their working life. In this context, the work is a reference: If the resources of the individual are in balance with the work, work ability will remain good. On the other hand, considering its central role, the employee mayhave benefits for health and ability to work based on actions to improve their working conditions. Objectives: 1) To analyze the contribution of different categories of working conditions (physical, psychosocial and environmental) on the association between occupational status and self-rated health, 2) propose and test an operationalization of the constructs involved in the new model of work ability in a sample of Brazilian workers. Materials and Method: We performed two studies, bothcross-sectional observational designs. The sample consisted of 5646 public employees of the city of Belo Horizonte that responded to a web survey in 2009. The questionnaire included self-rated health (very good, good, fair, poor/very poor), working conditions (physical demand, environment, psychological demand, control and support social at work) and sociodemographic and economic data. In the first study, a stereotype ordinal regression model stratified by gender was tested. The method is an extension of the multinomial regression model and allows comparingeach category of response variable with a reference category. In the second study, we use a structural equation modeling (SEM) to analyze the interrelationship between the work ability determinants. The method consists of a factor analyses and multiple regressions that allow the modeling of complex causality structures, taking measurement errors into consideration. Results: The results of first study showed that 24% of the workers rated their health as very good, 55% as good, 19% as fair and 2% as poor. The variables associated with poor self-rated health that remained in the women final model were: age, education, physical demand (Factor 2 - posture and weight management), environmental conditions (Factor 2 - ventilation, temperature, lighting and furniture), control and social support at work and occupational status. The result of the final model estimated for men were as follows: age, physical demand (factor 1 - fatigue or discomfort in general), environmental conditions (Factor 2 - ventilation, temperature, lighting and furniture), control andsocial support at work, psychological demand and occupational status. In both gender, the self-rated health was worse among those with lower occupational status confirming a situation of vulnerability among employees exposed to precarious working conditions. The influence of working conditions was different for men and women, but in general, the worst working conditions, worse self-assessment of health, regardless of age and occupational status. In the second study, the operationalization of Work Ability Model in a public employees sample showed that this construct is composed of multiple elements that interact in time and space in a multidimensional structure. The health was the important factor associated with work ability. Part of this effect is due to the influence of age and working conditions of public employees. In addition to this indirect effect, the work conditions exerted a direct effect on the ability to work. Considering the total effect (direct effect + indirecteffect), the construct work conditions was also a strong factor associated with work ability, confirming previous evidence. Conclusion: Based on results of first study, the public employees with lower occupational status or poorer working conditions had a higher chance of assess their health as poor. The shape and magnitude of health inequalities depended on gender and the work conditions. Improving environmental conditions and increasing job control and social support at work provide potential general interventions to reduced inequalities in health among these public employees. Physical and psychological demands may vary with the gender and content of the work and should be analyzed in specific contexts. In the second study, the SEM results founded a relationship pattern consistent with the Work Ability Model proposed by the Finnish Institute of Occupational Health (FIOH). The model presented appropriate fit indexes, confirming the fact that work ability should be understood as the result of dynamic interactions between the individual and his/herenvironment, as well as his/her experiences and habits, which contribute to his/her context. In conclusion, the studies carried out confirm the growing recognition of precarious working conditions in the municipal public service. Furthermore, provide evidences of negative consequences on the self-rated health and work ability of public employees. The events investigated are nonlinear and the interacting with different groups and context, produce complex behavior, requiring comprehensive and contextualized solutions.